The Construction of Religious Moderation Based on Local Wisdom: A Study of the Samin Community in Blora - Rohim Habibi (Al-Jadwa: Jurnal Studi Islam, 2026)
The dominance of state-centric approaches in religious moderation discourse often overlooks organic conflict resolution mechanisms at the grassroots level, creating a gap between policy and cultural reality. This study aims to explore the social construction and actualization of religious moderation rooted in local wisdom within the Samin (Sedulur Sikep) community in Blora. Employing a phenomenological approach grounded in Peter L. Berger’s Social Construction Theory, this research gathered data through in-depth interviews with ten key Samin figures (Sedulur Sikep) and participatory observations in the Kemantren areas. The results reveal that Samin moderation is not built upon theological dogma, but on the dialectic of Laku (praxis) philosophy and anti-panasten (self-restraint). This construction shifts the paradigm from ritual piety to substantive social piety. Specifically, these values manifest in three key dimensions: (1) radical honesty (nemu wae ora keno), (2) inclusive traditions establishing an interfaith peace zone, and (3) political resilience against sectarian polarization. This study concludes that Saminism offers a bottom-up moderation model that strengthens national commitment. Consequently, religious moderation policies should integrate these grounded cultural pathways to enhance social cohesion beyond formal theological dialogues.